ChemInform Abstract: Catalytic Intermolecular Hydroacylation of C‐C π‐bonds in the Absence of Chelation Assistance. Issue 5 (13th February 2013) - Leung, Joyce C.; Krische, Michael J.
Abstract Review: 145 refs.